Analisis Perubahan Garis Pantai Pesisir Pantai Dumai - Tiurma Monalisa Siahaan; Manyuk Fauzi; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Dumai Coast is directly facing Malacca Strait that its prone to damage. Coastal vulnerability analysis was carried out to know the coastal vulnerability index of Dumai Coast and useful as a first step to cope with the damage.The paper presents a method for integrating Coastal Vulnerability Index (CVI), and Geographic Information system (GIS) technology to map the coastal vulnerability.Emphasize has been made to the method-ological aspect, essentialy which is linked to:The use of GIS technique for constructing, interpolation, filtering, and resampling the data for shoreline gird. This research was conducted on the Coast Dumai along 107 km with the coordinates 101º 0’ 38” - 101º 43’ 33” East Longitude, 01º 26’ 50” - 02º 15’ 40” North Latitude. Coastal vulnerability index is calculated with the value of the physical variables such as shoreline changes, the length and width of the damage, the width of the green belt, wave height, tidal range, land use, and coastal slope. The analysis of satellite imagery is to analyze shoreline changes, the length and width of the damage, the width of the green belt, tidal range, and land use. The hydro-oceanography data is used for tha analysis of wave height and bathymetry data is used for tha analysis of coastal slope. Results of analysis showed that Pelintung Village, Mundam Village, Teluk Pulau Hilir Village, Village Bangko kanan, Basilam Baru Village, and Batu Teritip Village have low coastal vulnerabilty (0 < CVI < 25). Guntung Village and Dumai have moderate coastel vulnerability (25 < CVI < 50)Keywords: Satellite Imagery, Hydro-oceanography, Bathymetry, Coastal vulnerablity Index (CVI). Dumai Coast